Des coopératives minières équitables ? Difficultés et réajustements de la filière « équitable » dans les mines aurifères artisanales et à petite échelle en Bolivie. - Claude Le Gouill; Hernan Herbozo (VertigO)
In 2010, the Cotapata cooperative in Bolivia was the first artisanal mining organisation to sell "fair trade" gold globally, followed in the country by the "15 de agosto" cooperative and Yani. In all three cases, however, the miners decided not to maintain the certification after a few years, in the context of a gold rush that was heavily criticised for its labour practices and environmental consequences. After describing the difficulties in developing this certification, we will show how the institutions involved in the responsible gold approach in Bolivia have taken account of these failures to reorient their framework of action more directly towards penetrating the 'frontiers' of artisanal gold mining in Bolivia, according to a model of 'progressive adaptability' that takes into account local mining contexts. This framework is aimed more at formalising cooperatives and establishing socio-environmental education work with miners, based on a more horizontal approach that partly breaks the top-down processes of fair-trade certification.